Comparison between the American code ASCE7-16 and the Australian code AS1170.4 against the seismic design effects - AL-OBAIDI, ALI (2018)
Engineering is a professional art of applying science to the efficient conversion of natural resources for the benefit of man. Engineering, therefore, requires above all creative imagination to the innovative, useful application for natural phenomenon.” (International Journal of Engineering Research & Technology (IJERT), Vol. 3 Issue 3, March – 2014). This work implemented to compare two codes, American and Australian by designing a sixty -floors building using reinforced concrete structure from the economic point of view. Two critical structural codes adopted, ASCE-7 16 and AS1170. These codes compared in term of strength design necessities of structure elements and the shear design included as well. During this study, calibration and elaboration of the models adopted along with the criteria consecration revealed. Though the main principles are the same and the seismic zone will moderate, the details were different and made the comparison accurately, the analysis implemented via ETABs software from CSI Company established in the USA. This work will show the development of the Australian code especially for the earthquake loading using the AS1170.4, 2007. The Australian engineers established new response spectrum design contains a better illustration of the acceleration, displacement and velocity for the type of site soil (soft and rock). The used procedure to establish the spectrum could use in another country which has a low/ moderate seismicity. The AS1170.4 used a tiered approach for the earthquake load starting from simple force to complicated displacement method. One of the significant advantages of this method especially on the low seismic zone is given the engineers to design against the vertical and wind loads then perform the displacement checking for the earthquake impact. In parallel, the ASCE-7 16 deliver the all the possible design requirements for general structures along with the dead, live, snow, flood, rain, soil, wind load, and atmospheric ice with the proper combinations which is fit for the building code. The standard is a revision of ASCE-7 10 which is a revision of ASCE-7 5 respectively and it's providing a full update and re-arranged of the wind load. Also, it has a new ultimate wind load maps along with the reduced load factors and it has an update on the risk targeted seismic maps. This standard is a comprehensive and important version as a part of the building codes which are used in the United States.